The Rights of Nursing Mothers at the Workplace in the Perspective of Public Service and Its Effect on Job Performance - Sri Juni Woro Astuti; Esa Wahyu Endarti (Universitas Sebelas Maret, 2021)
This study aimed to examine whether the rights of nursing mothers at work have been fulfilled from a public service perspective and how this will affect their job performance. Mother’s role determines the quality of the next generation that depends on the quality of education and health provided to her children from an early age. From a health aspect, a mother must provide adequate nutrition from an early age through breast milk. Based on WHO recommendations, the Indonesian government recommends mothers to exclusively breastfeed for six months. From a legal aspect, the Indonesian government has provided protection rights for nursing mothers, as regulated in Law Number 13 of 2003 concerning Manpower. However, the phenomenon shows that more working mothers leave their children without breast milk and rely on their babies' nutrition from canned milk. This study uses a mixed methods. The population is female workers who have babies between 1 and 6 months age. Sample determined by a convenience method. Collecting data using questionnaires, interviews and secondary data. A total of 176 respondents have meet the criteria. In addition, we entered secondary data through digital document tracing. Data analysis was descriptive and triangulated with secondary data, then analyzed interactively to conclude. The results showed that the rights of mothers to breastfeed exclusively at work for 6 months have not been fulfilled properly. This finding supports the results of previous studies where adequate quality of care for nursing mothers will contribute to the performance of nursing mothers in the workplace.